Development of method for frequency regulation of output current in high-voltage transformerless resonant chargers of capacitive energy storage devices - Vinnychenko, Dmytro; Nazarova, Natalia; Vinnychenko, Iryna (Eastern-European Journal of Enterprise Technologies, 2024)
The object of research is high-voltage systems of electric discharge installations for various technological purposes. The work reports solving the problem of enabling the rate of charging of a capacitive energy storage, set by the requirements of a certain high-voltage technology. The quantitative characteristics of the deviation of the output current of the resonant inverter from the set stabilized value when changing the switching frequency of inverter switches in the range of output voltage change from 0 to 20 kV were determined. Using the Fourier transform of the rectangular input voltage, the frequency regulation possibility of the output current of the charger for capacitive energy storage devices was analyzed. Estimation dependences of the output current of resonant inverter on the load resistance and frequency deviation from resonant frequency were derived. These dependences could be used to implement frequency control over the switching inverter transistors, with the help of which the given effective value of the output current of the resonant inverter is obtained. A method of frequency regulation of the output current in high-voltage transformerless resonant charging devices of capacitive energy storage devices has been developed. Special feature of this method is that it is based on the frequency dependence of reactive resistances of the inductance and capacitance of the resonant circuit connected in series. Owing to that, it makes it possible to adjust the switching frequency of the inverter’s power switches depending on the relative resistance of the load and the specified growth rate of the capacitive energy storage voltage. The results reported here could be used in the design of benches for testing the electrical strength of high-voltage cables, as well as for the construction of high-voltage transformerless chargers in systems of electric discharge impulse processing of materials